Quality of a MOOC inclusion on education: implementation of various instruments and indicators - Patricia Gómez Hernández; Carlos Monge López; Eladio Sebastián Heredero (Universidade Estadual Paulista Júlio de Mesquita Filho, 2016)
In the XXI century, the need of training in, for and with Information and Communication Technologies seems significant. In this contextual framework, there are two highlighted elements: the Massive Open Online Courses, and the inclusive school. Thus, the main aim of this study is to evaluate a MOOC from Iberoamerican context that emphasizes the attention to diversity from an approach based on inclusive education. For this reason, the case study was used as research method, standing out the application of several assessment instruments in relation to quality criteria of MOOCs. In general, the results highlight a positive evaluation around almost all analyzed dimensions and subdimensions, particularly around pedagogical aspects. In conclusion, there is a MOOC in the Iberoamerican context that discusses the inclusive education, which has been valued very positively, although it must continue to improve.